Hak wasiat anak dalam kandungan perspektif hukum Islam - Nizami, Auliya Ghazna (Universitas Negeri Yogyakarta, 2020)
This study discusses the waá¹£iya right of the fetus (janÄ«n) in the context of Islamic law. Islamic law in this regard is the opinion of the most powerful jurists in the four best known sects (maÅ¼hab). Being something that is worth mentioning is due to the lack of human attention and the legality that surrounds it to the rights of janÄ«n. This study aims to find out how Islamic law protects the rights of children in the content with the strongest opinions available. This research is a literature study by collecting data in classic jurisprudence books to find out the opinions and opinions of past jurists and other supporting articles, normative jurisprudence that seeks to extract values and norms from the opinions of classical jurists. or any of the arguments contained in the law, and uses a descriptive approach intended to illustrate in general the scope of Islamic law in relation to the rights of the janÄ«n. This study of Islamic law produces the strongest opinions of any internal debate in a sect, and the most salient opinion of all maÅ¼hab on a waá¹£iya right of the janÄ«n.